2020
DOI: 10.14192/kjicp.2020.25.1.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Routine Environmental Management and Additional Ultraviolet (UV) Disinfection Environmental Management in Hospital Operating Rooms

Abstract: Background: This study evaluated the effects of routine and additional environmental management with pulsed xenon ultraviolet (PXUV) disinfection in hospital operating rooms (ORs). Methods: The study was conducted in 10 ORs of a hospital specializing in joint surgery with 174 hospital beds. We selected four surfaces with high frequency and one surface with low frequency of contact with the hands of operating room medical staff. After regular environmental management and additional PXUV disinfection from March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Lisa Croke, Managing Editor concluded that a PXUV device should not replace standard cleaning, but it can be used to improve environmental disinfection. 8 In another study, researchers evaluated the effectiveness of a UVC disinfection system for terminal cleaning in the OR before and after standard manual chemical disinfection. The portable system emits UV light horizontally and vertically, has a floor lamp to expose the floor and the system's wheels, and is navigated by an operator protected by a UVC blocking shield.…”
Section: Whole-room Disinfection Using Germicidal Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Lisa Croke, Managing Editor concluded that a PXUV device should not replace standard cleaning, but it can be used to improve environmental disinfection. 8 In another study, researchers evaluated the effectiveness of a UVC disinfection system for terminal cleaning in the OR before and after standard manual chemical disinfection. The portable system emits UV light horizontally and vertically, has a floor lamp to expose the floor and the system's wheels, and is navigated by an operator protected by a UVC blocking shield.…”
Section: Whole-room Disinfection Using Germicidal Lightmentioning
confidence: 99%
“…Overall, 4.8% of cultures were positive after standard cleaning and 0.8% were positive after standard cleaning combined with use of the PXUV device. The authors concluded that a PXUV device should not replace standard cleaning, but it can be used to improve environmental disinfection 8 …”
Section: Effectiveness In Practicementioning
confidence: 99%